2020
DOI: 10.1021/acsinfecdis.0c00120
|View full text |Cite
|
Sign up to set email alerts
|

Enterovirus D68 Antivirals: Past, Present, and Future

Abstract: Enterovirus D68 (EV-D68) is an RNA virus that causes respiratory illnesses mainly in children. In severe cases, it can lead to neurological complications such as acute flaccid myelitis (AFM). EV-D68 belongs to the enterovirus genera of the Picornaviridae family, which also includes many other significant human pathogens such as poliovirus, enterovirus A71, and rhinovirus. There are currently no vaccines or antivirals against EV-D68. In this review, we present the current understanding of the link between EV-D6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 102 publications
(251 reference statements)
0
35
1
Order By: Relevance
“…In addition, immune suppressive therapies have also been used by some centers to target the inflammatory response to infection [ 131 ]. It should be noted that recently much progress has been made in the development of the EV-D68 antivirals by targeting various viral proteins and host factors essential for viral replication [ 132 ]. However, this intervention was not associated with improved neurologic outcomes [ 133 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, immune suppressive therapies have also been used by some centers to target the inflammatory response to infection [ 131 ]. It should be noted that recently much progress has been made in the development of the EV-D68 antivirals by targeting various viral proteins and host factors essential for viral replication [ 132 ]. However, this intervention was not associated with improved neurologic outcomes [ 133 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, most antiviral research has targeted this virus. Several antiviral strategies have been proposed (reviewed in References [ 165 , 166 ]) such as capsid-binding compounds [ 145 , 167 , 168 , 169 , 170 , 171 ], viral proteases’ inhibitors [ 168 , 169 , 172 , 173 , 174 ], drugs targeting the non-structural proteins 2C [ 168 , 175 , 176 ], 3A [ 167 , 168 , 169 , 177 ], the viral polymerase 3D [ 167 , 169 , 178 , 179 ] and drugs blocking translation [ 180 ]. However, even the most favourable candidates did not obtain promising results in the mouse models [ 175 , 181 ].…”
Section: Discussionmentioning
confidence: 99%
“…The viral proteins that are being exploited as targets to develop anti-EV-D68 agents are those for which inhibitors were selected in the anti-HRV drug discovery process, since their high degree of sequence conservation among different enteroviruses might allow for broad-spectrum antiviral activity. 104 As an example, fluoxetine-modified inhibitors with broad spectrum activity against enteroviruses and rhinoviruses have been reported that target the non-structural 2C protein. 105 This protein has been proposed to play multifunctional roles in the viral life cycle of nonpolio enteroviruses, and significant efforts are being made in identifying antivirals against this target.…”
Section: Rhinovirusesmentioning
confidence: 99%